2014
DOI: 10.1039/c3gc42422g
|View full text |Cite
|
Sign up to set email alerts
|

Engineering plant cell walls: tuning lignin monomer composition for deconstructable biofuel feedstocks or resilient biomaterials

Abstract: Advances in genetic manipulation of the biopolymers that compose plant cell walls will facilitate more efficient production of biofuels and chemicals from biomass and lead to specialized biomaterials with tailored properties. Here we investigate several genetic variants of Arabidopsis: the wild type, which makes a lignin polymer of primarily guaiacyl (G) and syringyl (S) monomeric units, the fah1 mutant, which makes lignin from almost exclusively G subunits, and a ferulate 5-hydroxylase (F5H) overexpressing li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
43
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 32 publications
3
43
0
2
Order By: Relevance
“…Reduction in lignin content is known to improve sugar release from biomass upon treatment with cocktails of polysaccharide hydrolases (Studer et al, 2011), and similar beneficial effects have recently been reported to arise from modifications to lignin composition (Li et al, 2010b;Mansfield et al, 2012b;Ciesielski et al, 2014). We observed that of the four variants examined with low lignin content, cadc cadd and fah1 cadc cadd have the highest enzymatic cellulosic conversion for nonpretreated Arabidopsis inflorescence tissue.…”
Section: Increasing Aldehyde Content Correlates With Increased Potentmentioning
confidence: 52%
See 1 more Smart Citation
“…Reduction in lignin content is known to improve sugar release from biomass upon treatment with cocktails of polysaccharide hydrolases (Studer et al, 2011), and similar beneficial effects have recently been reported to arise from modifications to lignin composition (Li et al, 2010b;Mansfield et al, 2012b;Ciesielski et al, 2014). We observed that of the four variants examined with low lignin content, cadc cadd and fah1 cadc cadd have the highest enzymatic cellulosic conversion for nonpretreated Arabidopsis inflorescence tissue.…”
Section: Increasing Aldehyde Content Correlates With Increased Potentmentioning
confidence: 52%
“…On the one hand, several plants with disruptions in lignin content exhibit an increase in cell wall digestibility, although the reduced lignin has been correlated with decreased yield (Bonawitz and Chapple, 2013). On the other hand, plants with perturbations that affect lignin composition show improvements in cell wall degradability; however, this increase is sometimes only detectable after pretreatment (Li et al, 2010b;Ciesielski et al, 2014). Lignin composition is plastic and several genetic manipulations have generated plants with nearly homogeneous lignin subunit profiles or lignins derived from noncanonical monomers.…”
Section: Discussionmentioning
confidence: 99%
“…Theo verexpression of F5H with apowerful lignin promoter (entry 27) leads to al ignin almost exclusively composed of S-units,w hereas downregulation or deficiencies in F5H (entry 28) results in ap redominance of G-units. [117] However,i nb oth cases in Arabidopsis,adecrease in plant stiffness,c aused by the lack of secondary plant wall structure in the interfascicular and Table 2: Summary of reported genetic modificationswithin the phenylpropanoid pathway and their effects on saccharification yield, total lignin content, lignin composition/structure (and/or the effect on metabolites) and plant phenotype;TG(transgenic), M(mutation), ND (not determined).…”
Section: Bioengineered Ligninsmentioning
confidence: 99%
“…[117] Tw oc lasses of O-methyltransferases,t he so-called CCoAOMT and COMT enzymes (Scheme 1), are involved in producing the 3-and 5-methoxyl groups on Ga nd S monomers.5 -Hydroxyconiferaldehyde,w hen 5-O-methylation is deficient, reduces to 5-hydroxyconiferyl alcohol that is then integrally incorporated into lignins in COMT-deficient plants (entries 23 and 24). Ther esulting 5-hydroxyguaiacyl units react by typical 4-O-b-coupling with any of the hydroxycinnamyl alcohol monomers (the prototypical monolignols or further 5-hydroxyconiferyl alcohol), but the internal trapping of the intermediate quinone methide product by the novel 5-OH results in the formation of benzodioxane structures in the polymer.…”
Section: Entry Speciesmentioning
confidence: 99%
“…Since lignin is essential to support the plant and transport water and nutrients from the roots toward the leaves, large reductions in lignin content result in undesired phenotypes such as dwarfism [136]. Nevertheless, rather than reducing lignin content, changing the structure of the lignin polymer might be another elegant way in order to diminish cell wall recalcitrance [137,138]. Lignin enriched in S-units is more easily removed and more accessible to hydrolytic enzymes, and Arabidopsis plants with high S-lignin content released more glucose after pretreatment compared to G-lignin enriched plants [139].…”
Section: Lignin Modificationmentioning
confidence: 98%